PENERAPAN MEDIA AUDIO VISUAL DALAM MELATIH PERKEMBANGAN SENI UNTUK KELOMPOK B DI TK SA’ADDATUTDARAIN - Harjanty, Rokyal; Fitriani, Laily (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
Application of Audio-Visual Media in Training Art Development for Group B at Sa'addatutdarain Kindergarten. Learning the art of dance can be done in various ways, one of them was by using audio-visual media. Motion audio-visual media is a modern instructional media that is in accordance with the times (advancements in science and technology) because it includes vision, hearing and movement. The formulation of the problem is: How is the application of dance learning in Sa'addatutdarain Kindergarten with the use of audio-visual media? The purpose of his research in this study was: To find out how to apply dance learning in Sa'addatutdarain Kindergarten with the use of audio-visual media. The research method used in this research was descriptive qualitative. The subjects of this study were 1 school principal and 1 teacher. The results of the study show that art learning for early childhood with the application of audio-visual media in group B at Sa'addatutdarain Kindergarten has developed well, and teachers provide motivation to children so that children want to do the art being taught.